Completion of Past Gross Human Rights Violations: A Possibility of Foreign Assistance - Heribertus Untung Setyardi (UNIVERSITAS PGRI YOGYAKARTA, 2022)
Abstract Past gross human rights violations that occurred in Indonesia have not yet been resolved by the Government of Indonesia. The main obstacle was the establishment of an ad hoc Human Rights Court according to Law No. 26 of 2000. In this regard, this article would like to propose a number of reasons that can justify that the time has come for gross human rights violations to be resolved with the help of foreign parties, namely by using international dispute resolution mechanism. The reasons that can be used are that Indonesia unwilling and/or unable to resolve gross human rights violations, the obligations of Erga Omnes and the application of Universal Jurisdiction principles, and state sovereignty. Keywords: Gross Human Rights Violations, International Dispute Resolution Mechanism, Indonesia